Transition practice for primary immunodeficiency diseases in Southeast Asia: a regional survey - Chan, Chee Mun; Abdul Latiff, Amir Hamzah; Noh, Lokman Mohd; Ismail, Intan Hakimah; Abd Hamid, Intan Juliana; Liew, Woei Kang; Zhong, Youjia; Suratannon, Narissara; Nantanee, Rapisa; Santos-Ocampo, Fatima Johanna; Castor, Mary Anne R.; Nguyen-Ngoc-Quynh, Le; et al. (Frontiers in Immunology, 2023)
Introduction: With increased diagnostic capabilities and treatment modalities in the field of primary immunodeficiencies (PID), many pediatric patients survive beyond childhood and experience a change of care to the adult-oriented healthcare system. Unfortunately, the transition pathways for PID are less clearly defined, resulting in deterioration of quality of care in adulthood. Hence, this is the first regional study to address PID clinicians’ opinions on practices and challenges of transition care in 7 Southeast Asia (SEA) countries. Methods: We adopted a cross-sectional study design through an online survey platform to enquire opinions of transition practices from expert representatives in 7 SEA countries. Results: Regionally, 3 out 7 countries reported having no practice of transition care. Among cited challenges were reluctant adaptation by patients and caregivers to unfamiliarized adult healthcare systems, inadequate ratio of adult immunologists to patients and lack of facilities for transfer. Discussion and conclusion: Our study provides evidence to advocate policy makers on the importance of standardized integration of transition practice towards betterment of transiting PID patients into adulthood.